2019
DOI: 10.1111/idh.12391
|View full text |Cite
|
Sign up to set email alerts
|

An eight‐month randomized controlled trial on the use of intra‐oral cameras and text messages for gingivitis control among adults

Abstract: Objective To investigate the effects of using an intra‐oral camera (IOC) during a dental hygiene consultation and mobile text messages (TM) between appointments on clinical, behavioural and psychological parameters of patients with gingivitis. Materials and methods Patients were randomly assigned into four conditions: IOC, TM, IOC + TM and control, and examined at three assessment points over eight months (N = 142). Bleeding on marginal probing (BOMP), dental hygiene (brushing and flossing) and social cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 47 publications
(70 reference statements)
0
20
0
5
Order By: Relevance
“…The use of photographs and videos captured by the IOC in a dental appointment can contribute to improved gingival health, oral hygiene behaviors, and perceived self-efficacy 66. Similarly, an eight-month randomized control trial on the use of IOC and text messages for the control of gingivitis showed that using IOC during consultation and text messages between appointments improves clinical, behavioral, and psychological parameters of periodontal health 68…”
Section: Applications Of Iocmentioning
confidence: 99%
“…The use of photographs and videos captured by the IOC in a dental appointment can contribute to improved gingival health, oral hygiene behaviors, and perceived self-efficacy 66. Similarly, an eight-month randomized control trial on the use of IOC and text messages for the control of gingivitis showed that using IOC during consultation and text messages between appointments improves clinical, behavioral, and psychological parameters of periodontal health 68…”
Section: Applications Of Iocmentioning
confidence: 99%
“…[1][2][3][5][6][7][8][9] Consequently, some have concluded that intraoral cameras were an important aid to providing high-quality dentistry. 4,[10][11][12][13][14][15] Studies have found improved occlusal caries detection using an intraoral camera 4,11 and improved restorative treatment decisions. 4,[10][11][12][13][14][15] Studies have found improved occlusal caries detection using an intraoral camera 4,11 and improved restorative treatment decisions.…”
mentioning
confidence: 99%
“…16 Willershausen et al's study demonstrated that intraoral cameras helped motivate patients to reduce plaque accumulation, as the intraoral camera group showed reduction of plaque levels when compared to the control group. 15 Considering all these indings, the University of Iowa College of Dentistry & Dental Clinics (UI-CODDC) purchased nine intraoral cameras for student use. Use of the intraoral camera has also been linked with signiicant improvements in patients' behavioral, psychological, and clinical determinants of gingivitis.…”
mentioning
confidence: 99%
See 2 more Smart Citations